2018
DOI: 10.7567/jjap.57.11ue01
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of in-situ dielectric permittivity measurement using precision probing technique

Abstract: This paper proposes a breakthrough in-situ dielectric permittivity measurement technique for a circuit substrate with various planar circuits on the substrate. The proposed technique uses a quasi-resonator at the backside of an RF probe, which is contacted at the middle of the feed line of the planar circuits. Dielectric permittivity is calculated using the difference between the resonance frequencies of two measurements with different probe-contact positions. The proposed technique can be used for the feed li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…Although previous studies have demonstrated the PBR method only for Al 2 O 3 in room temperature, 25,26) this study also investigates Ba 2 Ti 9 O 20 with different temperatures. Considering the increase in the transmission loss of the CPW TL, the impact of transmission loss cannot be neglected from the measured S-parameter.…”
Section: The Pbr Methods With Compensation Of Transmission Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies have demonstrated the PBR method only for Al 2 O 3 in room temperature, 25,26) this study also investigates Ba 2 Ti 9 O 20 with different temperatures. Considering the increase in the transmission loss of the CPW TL, the impact of transmission loss cannot be neglected from the measured S-parameter.…”
Section: The Pbr Methods With Compensation Of Transmission Lossmentioning
confidence: 99%
“…The PBR method requires precision control of the RF probe in the measurement process. [25][26][27][28][29][30][31] Figure 1 shows a schematic representation of the PBR method. A pair of RF probes were placed in contact with the coplanar waveguide (CPW) transmission line (TL), such that one probe was in contact with the edge while the other was in contact with the middle.…”
Section: Introductionmentioning
confidence: 99%
“…1 shows the constructed on-wafer measurement system for measurement frequencies ranging from 190 GHz to 340 GHz. The system set up for the measurement frequencies up to 110 GHz is shown in [8,9]. Table II lists the information of the measurement systems and conditions.…”
Section: Measurement Instrumentsmentioning
confidence: 99%
“…The measurement system was calibrated by thru-reflect-line (TRL) calibration with the commercialized ISS which is indicated in the table. The radio frequency signal detection technique was used for the probing procedure [8,9].…”
Section: Measurement Instrumentsmentioning
confidence: 99%
“…On the other hand, the PBR method generates pseudoresonance by controlling the position of the hf probe in precision on a coplanar waveguide (CPW). [16][17][18][19][20][21] The PBR method can suppress the dimensional error of a resonator because it is determined by the accuracy of the probe position, which is generally smaller than the manufacturing error of the resonator. In addition, the author developed an original measurement technique for minimizing variation in probe position to less than 1 μm.…”
Section: Introductionmentioning
confidence: 99%